Considerations on the research and dissemination of agricultural knowledge by the facultad de agronomía (2013)
In order to mark the 50-year-history of the Facultad de Agronomía of the Universidad Nacional de Colombia, this article reviews the beginning of agronomy in Colombia, the creation of the Facultad de Agronomía, the development of the Escuela de Posgrados, and the launching of the journal Agronomia Colombiana; and analyzes the prioritization of research as a function of undergraduate thesis and theses from 1970 to 2012 and of the articles published in Agronomia Colombiana for 30 years. The fruits of its labor show that the Facultad strengthened the discipline of Crop protection in its first two decades with important advances in crops of flowers and cacao and went on to strengthen the fields of Crop physiology, Plant breeding, Soil and water, Economy and rural development, resulting in diversification to fruits, vegetables, the potato, flower species and perennial crops, showing how the Facultad's mission of teaching, research and continuing education has contributed to the development of the agricultural sector in Colombia.